Africa Development Indicators 2011 - World Bank (World Bank, 2012)
This year's Africa development indicators, which covers some 1,700 macroeconomic, sectoral, and human development indicators dating to the 1960s, comes at a critical time for Sub-Saharan Africa's 48 countries and 841 million people. After a decade of economic growth at nearly 5 percent a year, Africa-along with the rest of the world-was hit hard by the global economic crisis, but it rebounded within a year. In 2011 the continent's growth is expected to return to pre crisis levels. The poverty rate has been declining at about one percentage point a year, and progress on the millennium development goals, while insufficient to reach the 2015 targets in many countries, has been substantial. Yet, Africa faces some of the most formidable development challenges in the world. First, growth has been uneven, with about 20 fragile and conflict affected states seemingly trapped in persistent poverty. Second, economic growth has not translated to productive jobs and more earning opportunities for Africa's labor force-most of which is engaged in agriculture and informal enterprises-and especially for the 7-10 million young people entering the labor force each year. And third, Africa's growth could be faster and more widespread if it could address its most fundamental challenges-improving governance and increasing public sector capacity. A tool for learning, capacity strengthening, and accountability, Africa development indicators 2011 will continue to play a critical role in Africa's economic transformation.